1988
DOI: 10.1007/bf00917156
|View full text |Cite
|
Sign up to set email alerts
|

Operation Everest II: Alterations in the immune system at high altitudes

Abstract: We investigated the effects on immune function after progressive hypobaric hypoxia simulating an ascent to 25,000 ft (7620 m) over 4 weeks. Multiple simultaneous in vitro and in vivo immunologic variables were obtained from subjects at sea level, 7500 ft (2286 m), and 25,000 ft during a decompression chamber exposure. Phytohemagglutinin-stimulated thymidine uptake and protein synthesis in mononuclear cells were reduced at extreme altitudes. Mononuclear-cell subset analysis by flow cytometry disclosed an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 18 publications
1
32
2
Order By: Relevance
“…Both in vivo and in vitro evidence suggests that hypobaric hypoxia decreases immunoreactivity, speci®cally by suppressing T-cell-mediated immunity (Meehan 1987(Meehan , 1988. Oxidative damage mediated by free radicals also increases at altitude (Simon-Schnass 1990;Vasankari et al 1997) which has implications for membrane integrity and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and in vitro evidence suggests that hypobaric hypoxia decreases immunoreactivity, speci®cally by suppressing T-cell-mediated immunity (Meehan 1987(Meehan , 1988. Oxidative damage mediated by free radicals also increases at altitude (Simon-Schnass 1990;Vasankari et al 1997) which has implications for membrane integrity and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally observed that this branch of immunity is only marginally affected by high altitude exposure [ 48 , 69 , 79 -81 ], although lymphopenia has been reported to occur with acute exposure to hypoxia [ 9 , 24 ] possibly as a result of the associated increase in cortisol. In the Operation Everest II study cited above, it was reported that no differences were found at any altitude in polyclonal B-cell function [ 48 ]. After 9 days at altitude, no differences in spontaneous or pokeweed mitogen (PWM)-stimulated IgA, IgG, or IgM production were found.…”
Section: Il-6 (Pg/ml)mentioning
confidence: 87%
“…T-cell subsets carry out a variety of immunological functions including helper, suppressor, and cytotoxic (killing cells already infected with viruses and other intracellular pathogens). The literature clearly indicates that cell-mediated immunity and T lymphocyte function is the branch of the immune system most adversely affected by acute exposure to high altitude [ 48 ]. Several investigations involving human subjects suggest that acute exposure Fig.…”
Section: Adaptive Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…High altitude exposure influences much immune function (Mazzeo et al, 1994;, including mobilization of T-cells and NK cells, and regulation of cytokine production and release (Klokker et al, 1993;Pedersen and Steensberg, 2002). Regardless of the mechanism, it appears clear that acute exposure to altitude/hypoxia results in alterations of specific components of the immune system (Meehan et al, 1988;Klokker et al, 1993;Mazzeo et al, 1994;Steensberg 2002, Facco et al, 2005). Recently, more attention has been directed toward examining the influence of hypoxia on inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%